Acute demyelinating encephalomyelitis and transverse myelitis in a child with COVID-19 - Poyrazoglu, Hatice Gamze; Kirik, Serkan; Sari, Mehmet Yusuf; Esen, Ihsan; Toraman, Zulal Asci; Eroglu, Yesim (Turkish J Pediatrics, 2022)
Background. Corona virus disease 2019 (COVID-19) includes a wide range of diseases with varying pathophysiology in children and adults. Although the disease mainly affects the respiratory tract, neurological involvement is also reported in the literature. The most common neurological complaints due to COVID-19 are headache, dizziness and anosmia. Acute necrotizing myelitis, acute demyelinating encephalomyelitis (ADEM), acute axonal neuropathy, acute transverse myelitis, and Guillian-Barre syndrome have been reported as neurological dysfunctions associated with COVID-19. Case. A ten-year-old male patient presented with complaints of fever, headache and generalized muscle pain. The patient developed inability to walk and significant muscle weakness during the disease course, and he was diagnosed with ADEM and transverse myelitis on magnetic resonance imaging (MRI). As the etiological agent, COVID-19 was detected in both the respiratory panel sample and the cerebrospinal fluid (CSF) sample by the polymerase chain reaction (PCR) technique. Pulse steroid, IVIG, and plasmapheresis treatment were administered. He started to stand with support during follow-up. Conclusion. We presented a case of COVID-19 related ADEM and transverse myelitis who responded to pulse steroid, IVIG, and plasmapheresis
Keywords: acute demyelinating encephalomyelitis; acute transverse myelitis; COVID-19